KEBERPIHAKAN PEMERINTAH KOTA JAMBI PADA MASYARAKAT MISKIN PERKOTAAN - Riri Maria Fitriani; Makmun Wahid; Ratna Dewi (Universitas Nasional, 2018)
This study describes and analyzes the alignments of the Jambi City Government to ensuring education and health for the urban poor society at Jambi city. To see whether or not the government has succeeded in carrying out those function, this research will try to reveal it through the implementation of social security in the case of education and health services in Talang Gulo’s Final Waste Disposal Area, Jambi City. This study uses a type of qualitative research with case study approach that is intrinsic case study to find out more about the alignments of the Jambi City government to those who have been far from the reach of government programs. The results of this study are miscoordination between the private sector, and the government in organizing social security. The poor society in Jambi City do not get good social security to live a good life and there is a kind of poverty culture in Talang Gulo which can be seen from some of the poor communities in the region who think their lives are quite like now or in other words structural poverty. The research findings illustrate that the State has failed in organizing social security as a strategy to overcome the welfare problems of the community, especially for those who live below the poverty line.Keywords: Destitution, Urban, Social Security